1968
DOI: 10.1002/ar.1091610105
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis and ovarian development in the prenatal pig

Abstract: Gametogenesis and ovarian development were examined by means of histologic, cytologic and radioisotopic techniques in porcine ovaries of ages ranging from 13 days post coitum (PC) to birth (114 days PC). Limited observations were made i n postnatal ovaries (birth to 130 days post parturn).Primordial germ cells were noted at 18 days PC in the region of the germinal ridge (border of mesonephros) seven days prior to its formation (24-25 days). Meiosis began as early as day 40 in some cases and was a characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
2
5

Year Published

1975
1975
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 14 publications
2
46
2
5
Order By: Relevance
“…Deanesly (1975,1977) found that, in the horse, the first groups of oocytes degenerate and disappear and that, much later, peripheral oogonia develop into oocytes and eventually normal primordial follicles. Black & Erickson (1968) and Mauleon (1969) suggested a similar pattern in other eutherians. In the tammar there is no such disruption of germ cell development although some degeneration was noted early in each wave of successive stages.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Deanesly (1975,1977) found that, in the horse, the first groups of oocytes degenerate and disappear and that, much later, peripheral oogonia develop into oocytes and eventually normal primordial follicles. Black & Erickson (1968) and Mauleon (1969) suggested a similar pattern in other eutherians. In the tammar there is no such disruption of germ cell development although some degeneration was noted early in each wave of successive stages.…”
Section: Discussionmentioning
confidence: 60%
“…Detailed descriptions of the early pattern of development of female germ cells have been published for several species of eutherian mammals, including the rat (Beaumont & Mandi, 1962), man (Baker, 1963), guinea-pig (Ioannou, 1964), rhesus monkey (Baker, 1966), pig (Black & Erickson, 1968), sheep (Mauléon, 1969(Mauléon, , 1975, horse (Deanesly, 1975(Deanesly, , 1977 and calf (Prépin, Jost & Vigier, 1977). By contrast, accounts of germ cell development in female marsupials are very restricted.…”
Section: Introductionmentioning
confidence: 99%
“…How the FOXO3 level increases in prepubertal porcine ovaries is not well understood. Prepubertal porcine ovaries contain a large number of developing follicles (Black & Erickson 1965). Developing follicles are found in well-vascularized cortical-medullary borders, whereas primordial follicles are located in a relatively avascular region in the cortex (Gougeon 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The ovaries of infant pigs contain a large number of primordial follicles and also a small population of developing follicles that contain growing oocytes. Primordial follicles represent more than 95% of the total follicular proportion in porcine ovaries at 2 weeks after birth (Black & Erickson 1965, Oxender et al 1979. The ovaries of prepubertal and adult animals possess numerous growing and fully grown oocytes in the developing and mature follicles respectively, as well as a number of nongrowing primordial oocytes as the future stock.…”
Section: Introductionmentioning
confidence: 99%
“…The oocytes of large animals are relatively large in size and have a long growth phase. For example, the period from initiation of the primordial follicle development to the final preovulatory stage takes several months in pigs [2]. Therefore, in vitro growth of oocytes in the primordial follicles of large animals is still challenging.…”
mentioning
confidence: 99%